2019
DOI: 10.1111/trf.15585
|View full text |Cite
|
Sign up to set email alerts
|

Human red blood cell stroma: an alternative to traditional allogeneic adsorption methods

Abstract: ABBREVIATIONS: DAT = direct antiglobulin test; EGA = ethylenediaminetetraacetate glycine acid; IAT = indirect antiglobulin test; PEG = polyethylene glycol; wAIHA = warm autoantibody immune hemolytic anemia. From the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, the efficiency of the adsorption was related to the number of Daudi cells used, suggesting the existence of a threshold above which the number of cells used is high enough to provide a sufficient number of CD38 molecules to allow binding to DARA and result in an efficient depletion. 17 Wilson and Branch 10 have recently shown that human RBC stroma prepared using digitonin is an efficient and effective method to remove autoantibody reactivity and allow detection of potentially clinically significant antibodies. In light of that study, and the demonstration of an effective DARA depletion using intact Daudi cells, we have prepared Daudi cell stroma using a sonication based method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the efficiency of the adsorption was related to the number of Daudi cells used, suggesting the existence of a threshold above which the number of cells used is high enough to provide a sufficient number of CD38 molecules to allow binding to DARA and result in an efficient depletion. 17 Wilson and Branch 10 have recently shown that human RBC stroma prepared using digitonin is an efficient and effective method to remove autoantibody reactivity and allow detection of potentially clinically significant antibodies. In light of that study, and the demonstration of an effective DARA depletion using intact Daudi cells, we have prepared Daudi cell stroma using a sonication based method.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Daudi stroma adsorption has additional advantages such as reduced dilutional effects due to efficient packing of the stromal adsorption material and potentially long shelf life, because it can be frozen for months, as demonstrated by previous studies that used human stroma. 10 However, this method requires special equipment such as ultrasonic processor and tabletop centrifuge with performance up to 20 000g, which could impact its broader use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation